Habitat suitability of neotenic net-winged beetles (Coleoptera: Lycidae) in China using combined ecological models, with implications for biological conservation - Liu, Tong; Liu, Haoyu; Tong, Junbo; Yang, Yuxia (Diversity & distributions, 2022)
Aim China has dozens of well‐recognized biodiversity hotspots, but many more potential areas have not been estimated thoroughly, which is unfavourable for biodiversity conservation. Neotenic net‐winged beetles with limited dispersal ability generally occur in restricted ranges but rarely occur in China, which makes them ideal models for biogeographical studies to define biodiversity hotspots. This study will explore the potential distribution patterns of neotenic Lycidae in China to provide basic data for the implementation of biological conservation. Location China. Methods We conducted maximum entropy (MaxEnt) and random forest (RF) modelling to simulate the habitat suitability for neotenic Lycidae occurring in China under different climate scenarios by using all available distribution information in Southeast Asia (a total of 305 occurrence records) and several environmental variables. The dynamic changes in the potentially suitable habitats and centroids of neotenic Lycidae were simulated under all climate scenarios. Results The results indicated that potentially suitable habitats for neotenic Lycidae were mostly located in the montane areas and mountainous islands in southern China, including the eastern Himalayas, Gaoligong Mountains, Ailao Mountains, Hengduan Mountains, Wumeng Mountains, Miaoling Mountains, Daba Mountains, Wu Mountains, Yunkai Mountains, Wuzhi Mountains and Central Mountains. In addition, the dynamic analyses showed that their changes also occurred in montane areas, whose affinity and significance were confirmed in the biological conservation. Main conclusions Taking the unique neotenic Lycidae as the subject, we verify that several montane areas are biodiversity hotspots that have already been well‐recognized, while it is determined that some additional mountains could be potential hotspots. Therefore, more attention and biological conservation efforts should be used in these areas. In addition, using the ensemble modelling approach to identify potential distributions is a helpful tool to develop strategies for biological conservation, even if it has several limitations.